Mechanical Properties of Concrete with Clam Shell Powder (CSP) as Partial Cement Replacement. - Mahshuri, Yusof; Sinin, Hamdan; Aaliyawani Ezzerin, Sinin (Trans Tech Publications Ltd, Switzerland, 2023)
This research focuses on compressive strength of concrete containing different percentages of municipal waste clam shell powder (CSP). The amount of cement is replaced by 5%, 10% and 15% of CSP. The result obtained shows that the compressive strength increases with the CSP content. Concrete containing 15%CSP has lower compressive strength compared to those containing 5% and 10%CSP. The concrete containing 15%CSP is almost similar to the control concrete (with zero CSP).